Description of a new species of the genus Falsotrachystola Breuning, 1950 (Coleoptera: Cerambycidae, Lamiinae) - Wang, Yingqi; He, Tianlong; Wang, Ping; Wang, Wenkai (Zootaxa, 2023)
In this work, a new species of the genus Falsotrachystola Breuning, 1950 (Cerambycidae: Lamiinae) is described and illustrated, namely Falsotrachystola xui sp. nov. from Guangxi Zhuang Autonomous Region and Guizhou province, China.